CFD analysis of jet flows ejected from different nozzles - ATMACA, MUSTAFA (OXFORD UNIV PRESS, 2021)
Nozzles are widely used to control the rate of flow, speed, direction, mass, shape and pressure of the stream in connection with many different engineering applications. This paper presents the performance predicted by a computational fluid dynamic (CFD) model, which are 3D models that utilize parametric analysis, realizable k-epsilon turbulence models and experimental measurement for a jet. Jet flows are ejected from three different slot nozzles: round-shaped nozzle, rectangular-shaped nozzle and 2D-contoured nozzle. In this numerical study, velocities of free jets have been predicted for different axial distances from the nozzle exit in the range of 0.2 <= z/B <= 12 when center velocity at the nozzle exit. CFD simulation results are compared to experimental results from literature. These results are consistent with the existing experiments.
Keywords: nozzle; jet; CFD; turbulence; mean velocity; GEOMETRY